Kajian Persepsi Masyarakat Pada Pembangunan Pariwisata DSP (Destinasi Super Prioritas) Terhadap Tingkat Pendapatan Masyarakat Pada Objek Wisata Danau Toba - Ricchad Joy Samosir; Ita Pingkan F. Rorong; Dennij Mandeij (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This research aims to determine the impact of the study of super priority destination tourism development on the level of community income at the Lake Toba tourist attraction. This research method is descriptive qualitative research, with the population of the community around Lake Toba (Samosir Regency) who are experiencing the impact of the development of super priority tourism destinations, using data collection techniques through answering questions (questionnaires) and literature study methods. The data analysis method uses Miles & Huberman's interactive model analysis, starting from data collection, data reduction, data presentation, to the process of drawing conclusions. The results of this research show that the existence of the Lake Toba super priority destination development program has had a good impact on the community. The community can experience an increase in income after this program exists on Lake Toba.  And with this super priority destination program, the community is also given the opportunity to receive training as business actors in the tourism sector, and the community is actively involved as a provider of suggestions and input in planning and developing Lake Toba as a super priority destination.